2021
DOI: 10.1007/s10926-021-09983-6
|View full text |Cite
|
Sign up to set email alerts
|

A Worksite Self-management Program for Workers with Chronic Health Conditions Improves Worker Engagement and Retention, but not Workplace Function

Abstract: Purpose An increasing number of workers in the US have chronic health conditions that limit their ability to work, and few worksite interventions have been tested to improve worker coping and problem solving at work. The purpose of this study was to evaluate a worksite-based health self-management program designed to improve workplace function among workers with chronic health conditions. Methods We conducted a randomized, controlled trial of a worksite self-management program (“Manage at Work”) (clinicaltrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Linton et al 83 demonstrated that an injured worker's workplace supervisor can be trained in effective communication skills to facilitate the worker's RTW, similar to Palermo's 112 accounts of the work with parents of children in pain. More recently, Shaw et al 123 have also described a work-site health self-management intervention for workers with chronic health problems, including chronic MSK pain, and their employers in the United States. Although these approaches show promise and further trials are needed, they do illustrate potential opportunities for improving quality of life outcomes for people with chronic pain conditions when social or environmental contributors are identified and addressed as part of a treatment plan.…”
Section: Social or Environmental Aspects Of Treatmentsmentioning
confidence: 99%
“…Linton et al 83 demonstrated that an injured worker's workplace supervisor can be trained in effective communication skills to facilitate the worker's RTW, similar to Palermo's 112 accounts of the work with parents of children in pain. More recently, Shaw et al 123 have also described a work-site health self-management intervention for workers with chronic health problems, including chronic MSK pain, and their employers in the United States. Although these approaches show promise and further trials are needed, they do illustrate potential opportunities for improving quality of life outcomes for people with chronic pain conditions when social or environmental contributors are identified and addressed as part of a treatment plan.…”
Section: Social or Environmental Aspects Of Treatmentsmentioning
confidence: 99%
“…The nature of the intervention was a 10-session group educational workshop aimed at improving the pain and illness self-management strategies of workers, with a special focus on strategies that could be implemented during working hours. Group comparisons of intervention outcomes for the randomized trial have been published previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Though less common, there are some promising individual-focused evidencebased interventions for workers with chronic health conditions to promote wellbeing and work ability. These include, for example, chronic disease self-management programs adapted to the workplace (e.g., the Live Healthy, Work Healthy program; Haynes et al, 2022); a worksite group self-management program for workers with chronic health conditions (i.e., the Manage at Work program; Shaw et al, 2022); and a virtual coaching program to improve work ability and alleviate burnout in workers with chronic health conditions (Beatty & McGonagle, 2016;McGonagle et al, 2014b).…”
Section: Workplace Supports For Workers With Chronic Health Conditionsmentioning
confidence: 99%